2012
DOI: 10.17221/6345-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Effect of season and age on blood minerals, liver enzyme levels, and faecal egg counts in Nguni goats of South Africa

Abstract: ABSTRACT:The objective of the study was to determine the relationships between age of the goat and faecal egg counts, liver enzymes, and minerals in the wet and dry seasons in male and female Nguni goats of South Africa. Fifty-six female and forty male Nguni goats were used for the study. Faecal and blood samples were collected once in the dry (August) and wet (January) season. Faecal egg counts (FEC) were determined by the modified McMaster technique while trematodes were determined by the sedimentation metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 44 publications
2
6
1
Order By: Relevance
“…This is in accordance with conclusions by Egbe-Nwiyi et al (2000). Generally, most of the haematological parameters determined in our study were within the normal range for goats reported by other authors (Zumbo et al, 2011;Habibu et al, 2017).…”
Section: Discussionsupporting
confidence: 88%
“…This is in accordance with conclusions by Egbe-Nwiyi et al (2000). Generally, most of the haematological parameters determined in our study were within the normal range for goats reported by other authors (Zumbo et al, 2011;Habibu et al, 2017).…”
Section: Discussionsupporting
confidence: 88%
“…The parameters of SAT and ALT were consistent with the references reported that normal range of liver enzymes. The AST level was varied from 167 to 513 U/l while, ALT between 9 and 19 U/l (Rumosa-Gwaze et al, 2012). In the present study, G2 showed a significant decrease in AST (175.00U/l) and ALT (11.50 U/l) compared with G1 that obtained that AST (184.25 U/l) and ALT (15.50U/l).…”
Section: Blood Metabolite Parameterscontrasting
confidence: 38%
“…The parameters of AST and ALT were consistent with the references reported that normal range of liver enzymes. The AST level was varied from 167 to 513 U L -1 while, ALT between 9 and 19 U L -1 (Rumosa-Gwaze, Chimonyo, & Dzama, 2012). In this study, the SP group showed a significant decrease in AST and ALT compared with the control ones.…”
Section: Some Blood Components Of Rahmani Ewesmentioning
confidence: 60%